If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -5 = 11x + 4 Reorder the terms: -5 + 14x = 11x + 4 Reorder the terms: -5 + 14x = 4 + 11x Solving -5 + 14x = 4 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -5 + 14x + -11x = 4 + 11x + -11x Combine like terms: 14x + -11x = 3x -5 + 3x = 4 + 11x + -11x Combine like terms: 11x + -11x = 0 -5 + 3x = 4 + 0 -5 + 3x = 4 Add '5' to each side of the equation. -5 + 5 + 3x = 4 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 4 + 5 3x = 4 + 5 Combine like terms: 4 + 5 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| -28+15-22c=31 | | 5p-2=3p+4 | | -34-7=2 | | a-2.5=7 | | 3-2m=5 | | (3x+7)(12x-6)= | | n-18=-4n | | 4+2(x-3)=-8 | | -3x-8y=-23 | | 4*-2x+5=-2*4x+5 | | 8x=-10+34 | | 2-3n=14-4n | | 4b-1*7=5*7 | | 4*x+2y=16 | | 3{2y-0.3}=19.4-y | | 16=-8-9 | | 8+4+x=9+3 | | 5n-12=103 | | 40=9x-2+20x+5 | | 2=y+6 | | 40=9x-2+20x-5 | | 6{g+3}=-2{g+31} | | 7(2x+3)+5=14x+26 | | 3x+2.4=6 | | 5x=73 | | 42=.5(2x+8)(x+3) | | x+-56=-82 | | y=-x^2+4x+60 | | -6(4x+3)=-6(-4x-3) | | 29x=-58 | | 70+3x=93 | | 2x-7=20-7x |